Empfehlungen zur Implantation von bioresorbierbaren koronaren Scaffolds: Indikationen, Implantationstechnik und Nachsorge - Nef, H. M.; Möllmann, H.; Gori, T.; Elsässer, A.; Achenbach, Susanne (Der Kardiologe, 2015)
Bioresorbable scaffolds (BRS) are an option for treatment of coronary artery disease. Recent studies showed safety and efficacy; however, the long-term outcome and the potential advantages in comparison to drug-coated metal stents has to be evaluated in randomized trials. Due to the many theoretical benefits BRS are widely used in clinical practice. Nevertheless, a closer look at registries shows that unexpected events were mostly associated with procedural problems. Therefore, there are some important details regarding the implantation process even though BRS are not basically different from metal stents. This article on recommendations discusses the indications for BRS and the most important implantation techniques.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Coronary stenosis; Efficacy; Long-term course; Metal stents; Safety